Pradigastat disposition in humans: in vivo and in vitro investigations. (2nd December 2017) - Upthagrove, Alana; Chen, Jin; Meyers, Charles D.; Kulmatycki, Kenneth; Bretz, Angela; Wang, Lai; Peng, Lana; Palamar, Safet; Lin, Melissa; Majumdar, Tapan; Tran, Phi; Einolf, Heidi J.
Abstract: 1. Pradigastat is a potent and specific diacylglycerol acyltransferase-1 (DGAT1) inhibitor effective in lowering postprandial triglycerides (TG) in healthy human subjects and fasting TG in familial chylomicronemia syndrome (FCS) patients. 2. Here we present the results of human oral absorption, metabolism and excretion (AME), intravenous pharmacokinetic (PK), and in vitro studies which together provide an overall understanding of the disposition of pradigastat in humans. 3. In human in vitro systems, pradigastat is metabolized slowly to a stable acyl glucuronide (M18.4), catalyzed mainly by UDP-glucuronosyltransferases (UGT) 1A1, UGT1A3 and UGT2B7. M18.4 was observed at very low levels in human plasma. 4. In the human AME study, pradigastat was recovered in the feces as parent drug, confounding the assessment of pradigastat absorption and the important routes of elimination. However, considering pradigastat exposure after oral and intravenous dosing, this data suggests that pradigastat was completely bioavailable in the radiolabeled AME study and therefore completely absorbed. 5. Pradigastat is eliminated very slowly into the feces, presumably via the bile. Renal excretion is negligible. Oxidative metabolism is minimal. The extent to which pradigastat is eliminated via metabolism to M18.4 could not be established from these studies due to the inherent instability of glucuronides in the gastrointestinal tract.